Understanding RNA Flexibility Using Explicit Solvent Simulations: The Ribosomal and Group I Intron Reverse Kink-Turn Motifs - Sklenovský, Petr; Florová, Petra; Banáš, Pavel; Réblová, Kamila; Lankaš, Filip; Otyepka, Michal; Šponer, Jiří (Journal of chemical theory and computation, 2011)
Reverse kink-turn is a recurrent elbow-like RNA building block occurring in the ribosome and in the group I intron. Its sequence signature almost matches that of the conventional kink-turn. However, the reverse and conventional kink-turns have opposite directions of bending. The reverse kink-turn lacks basically any tertiary interaction between its stems. We report unrestrained, explicit solvent molecular dynamics simulations of ribosomal and intron reverse kink-turns (54 simulations with 7.4 μs of data in total) with different variants (ff94, ff99, ff99bsc0, ff99χOL, and ff99bsc0χOL) of the Cornell et al. force field. We test several ion conditions and two water models. The simulations characterize the directional intrinsic flexibility of reverse kink-turns pertinent to their folded functional geometries. The reverse kink-turns are the most flexible RNA motifs studied so far by explicit solvent simulations which are capable at the present simulation time scale to spontaneously and reversibly sample a wide range of geometries from tightly kinked ones through flexible intermediates up to extended, unkinked structures. A possible biochemical role of the flexibility is discussed. Among the tested force fields, the latest χOL variant is essential to obtaining stable trajectories while all force field versions lacking the χ correction are prone to a swift degradation toward senseless ladder-like structures of stems, characterized by high-anti glycosidic torsions. The type of explicit water model affects the simulations considerably more than concentration and the type of ions.